Color Stability and Surface Roughness of Composites After Artificial Accelerated Aging - da Silva, Raquel A. B.; Mellara, Talitha S.; Pires-de-Souza, Fernanda C.P; da Silva, Lea A.B.; Pucinelli, Carolina M.; Gatón-Hernández, Patrícia (UI Scholars Hub, 2017)
The color stability and surface uniformity are very important properties for dental aesthetics. Objective: To evaluate the color stability and surface roughness of different composites after artificial accelerated aging (AAA). Methods: Samples were made using the silorane-based Filtek P90 (3M-ESPE), nanohybrid Tetric N-Ceram (Ivoclar Vivadent), and GC Kalore (GC Company). Ceramic D. Sign (Ivoclar Vivadent) and Ketac N100 (3M-ESPE) resin-modified glass ionomer cement (RMGIC) served as controls. The values for color stability and surface roughness were recorded before and after AAA for non-C-UV (300 hours). Color stability was assessed as the difference between the coordinates obtained from the L*a*b* system. The surface roughness was analyzed with a rugosimeter. The surface value of each sample was taken as the average of these measurements. The one-way ANOVA and Tukey’s post-test with α=5% was used. Results: The greatest change in color stability occurred for the RMGIC (ΔE=18.7) and the least for ceramics (ΔE=2.1). No significant difference was noted among the composites (p>0.05). The surface roughness before and after AAA differed significantly only for the RMGIC (p<0.05). Conclusion: The two latest generation resins (Filtek P90 and GC Kalore) showed good results in terms of color stability and surface roughness for use in aesthetic restorations.